The cat with a feathery tail and other stories - Blyton, Enid (Award Publications London, 2005)
The Cat with a Feathery Tail and Other Stories by Enid Blyton is a delightful collection of whimsical tales featuring animals, magic, and imaginative adventures. The title story introduces a cat with an extraordinary feathery tail, sparking curiosity and amazement among other characters. The collection includes various short stories that blend fantasy and moral lessons, with playful animals, magical events, and mischievous characters at the heart of each tale. Blyton's signature warmth and simplicity shine through, making the book an enjoyable read for young children who appreciate stories filled with wonder and light-hearted fun.